PERSEPSI MASYARAKAT TERHADAP RESIKO BENCANA LONGSOR DI SEKITARAN BUKIT LAMPU KECAMATAN BUNGUS TELUK KABUNG KOTA PADANG - Sisi Pratama; Afdhal Afdhal (JURUSAN GEOGRAFI FIS UNP, 2023)
Abstrak 1) Public perception of the risk of landslides 2) Impact of environmental damage due to landslides (3) Efforts made by the community and government in overcoming the impact of landslides on environmental damage that occurs. This type of research is qualitative research. The data used is primary data. Primary data were obtained from direct interviews with the community in Bukit Lampu. The technique of collecting research data uses observation, interview, and documentation techniques. Data analysis techniques are data reduction, data presentation, and drawing conclusions. The results of this study are: (1) Public perception of the risk of landslides and environmental damage, people in the Bukit Lampu area already know that landslides can damage the environment but the community can't do anything. (2) As a result of the landslide disaster, the impact on environmental damage is increasing critical land, causing damaged roads, destroyed houses and also traffic disturbances due to the back and forth of operational vehicles and transporters going in and out of the Bukit Lampu area. (3) Efforts made by the government, the community, repairing damaged roads, registering damaged houses and getting compensation from the government, as the government is a form of responsibility.